Aplikasi Mobile Media Pembelajaran Rukun Shalat Fardu Menurut 4 Imam Mazhab - Nasution, M. Irwan Padli; Putri, Raissa Amanda; Nasution, Rizki Ansyari (Lembaga Yasin AlSys, 2022)
Prayer is a means of communication between a servant and the creator. Prayer has pillars that must be fulfilled as a measure of whether the prayer is valid or not. The pillars of prayer are prayer movements that must be done and should not be abandoned. The pillars of prayer are also taught in the science of schools. Madhhab is an understanding or school of thought that comes from the ijtihad of a mujtahid about law in Islam which is excavated from the verses of the Qur'an and Hadith. Low knowledge of it will create a new theory that results in many errors and is not in accordance with the Qur'an and Hadith. This study aims to create a mobile application for learning the pillars of prayer fardhu according to 4 priests of the school to increase students' knowledge about the pillars of prayer based on the theory of 4 priests of the school and not cause differences of opinion in the community. The learning media uses the MDLC (Multimedia Development Life Cycle) development model with 6 stages. This application was tested in black-box testing, the results of all aspects of this study were good.